Small heat shock protein interactions with in vivo partners - Collier, M (2018)
Small heat-shock proteins (sHsps) are part of a broad cellular sys- tem that functions to maintain a stable proteome under stress. They also perform a variety of regulatory roles at physiological conditions. Despite the multitude of sHsp targets, their interactions with partners are not well understood due to highly dynamical structures. In this thesis, I apply a variety of biophysical and structural approaches to examine distinct interactions made by the abundant human sHsps αB-crystallin and Hsp27. First, I find that αB-crystallin binds a cardiac-specific domain of the muscle sarcomere protein titin. A cardiomyopathy-causative variant of αB-crystallin is shown to disrupt this interaction, with demonstrated implications for tissue biomechanics. Next, I investigate the conformation and unfolding behaviour of another sarcomere-associated protein, filamin C, finding support for the hypothesis that it is mechanosensitive. This leads into an interrogation of the interaction between filamin C and Hsp27, which we find is modulated by phosphorylation of Hsp27. This modulation only manifests during filamin C unfolding, pointing toward a protective chaperoning mode against over-extension during mechanical stress. This finding is bolstered by up-regulation and interaction of both proteins in a mouse model of heart failure. I establish a system for similar studies of a third sHsp, cvHsp, which is muscle-specific and implicated in various myopathies but scantly understood at the molecular level compared to αB-crystallin and Hsp27. Finally, I probe the stoichiometries and kinetics of complexes formed between αB-crystallin and Hsp27 themselves, which co-assemble into a highly polydisperse ensemble. This involved the development of a high-resolution native mass spectrometry method for disentangling heterogeneous systems. Together these findings add to our understanding of the roles and mechanisms of ATP-independent molecular chaperones.